2002
DOI: 10.1144/gsl.sp.2002.205.01.22
|View full text |Cite
|
Sign up to set email alerts
|

Bowing of marble panels: on-site damage analysis from the Oeconomicum Building at Göttingen (Germany)

Abstract: The use of natural stone panels or cladding material for building facades has led to some durability problems, especially with marble slabs. To examine the effects of intrinsic and extrinsic parameters on bowing, a very detailed study was performed on the Oeconomicum Building at the University of Goettingen. In total 1556 panels from the whole building were measured with respect to bowing using a bow-meter. The variation of bowing ranges from concave (up to 23 mm/m) to convex (up to -11 mm/m). The variation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…The phenomenon is well known in marbles, having been observed in various scenarios from ancient gravestones (Grimm 1999) to modern buildings such as the Amoco building in Chicago, Oeconomicum building in Göttingen (Koch and Siegesmund 2002) or Finlandia Hall in Helsinki (Ritter 1992). A more recent summary of marble bowing is given by Siegesmund et al (2008a), in which the latest and the most important hypotheses debated in scientific literature are presented.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon is well known in marbles, having been observed in various scenarios from ancient gravestones (Grimm 1999) to modern buildings such as the Amoco building in Chicago, Oeconomicum building in Göttingen (Koch and Siegesmund 2002) or Finlandia Hall in Helsinki (Ritter 1992). A more recent summary of marble bowing is given by Siegesmund et al (2008a), in which the latest and the most important hypotheses debated in scientific literature are presented.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for the effectiveness of this process at the scale of large rock blocks can be found not just in nature (e.g., see Folk and Begle-Patton, 1982) but also in unwitting experiments created by architects who clad buildings in sheets of stone with insufficient regard to stone structure and intervening expansion joints. Thus, for example, Koch and Siegesmund (2002) described the bowing of 128Â67-cm marble panels at the University of Gfttingen resulting from preferred thermal expansion dictated by rock fabric (grain size, grain boundary configuration, shape, lattice of preferred orientation, and microcrack fabric). Because the panels were cut without regard to this fabric, postemplacement heating and cooling resulted in a complex web of expansion and contraction that could only be accommodated by the inward and outward bowing of the panels.…”
Section: Does Size Matter?mentioning
confidence: 99%
“…Others [18][19][20][21] emphasised the importance of moisture, and concluded that exposure to heating alone is not sufficient to explain the expansion and bowing of marble cladding. Koch and Siegesmund [22], demonstrated that the moisture content after a heating cycle apparently influences the intensity of marble degradation. During the laboratory test, they demonstrated that the moisture content after a heating cycle has an impact on the strain rate of the Italian marble.…”
Section: Introductionmentioning
confidence: 99%